A Pilot Study Investigating the Expression Levels of Pluripotency-Associated Genes in Rectal Swab Samples for Colorectal Polyp and Cancer Diagnosis and Prognosis - Ryan Wai-Yan Sin; Dominic Chi-Chung Foo; Deepak Narayanan Iyer; May Sau-Yee Fan; Xue Li; Oswens Siu-Hung Lo; Wai-Lun Law; Lui Ng (Stem Cells International)
Change in gene expression is inevitable in cancer development. With more studies demonstrating the contributions of cancer stem cells (CSCs) in colorectal cancer (CRC) development, this study is aimed at investigating whether rectal swab specimen serves as a tool for detection of dysregulation of CSC or stem cell (SC) markers and at evaluating its potential as a new promising screening method for high-risk patients. Expression levels of 15 pluripotency-associated genes were assessed by quantitative PCR in 53 rectal swab specimens referred for endoscopic screening. Dysregulated genes and joint panels based on such genes were examined for their diagnostic potentials for both polyp and CRC. Out of 15 genes, Oct4, CD26, c-MYC, and CXCR4 showed significantly differential expression among normal, polyp, and CRC patients. A panel of Oct4 and CD26 showed an AUC value of 0.80 (p=0.003) in identifying CRC patients from polyp/normal subjects, with sensitivity and specificity of 84.6% and 69.2%. A panel of c-MYC and CXCR4 achieved CRC/polyp identification with an AUC value of 0.79 (p=0.002), with a sensitivity of 82.8% and specificity of 80.0%. The sensitivity for polyp and CRC was 80.0% and 85.7%, respectively. Further analysis showed that higher c-MYC and CXCR4 level was detected in normal subjects who developed polyps after 5-6 years, in comparison with subjects with no lesion developed, and the AUC of the c-MYC and CXCR4 panel increased to 0.88 (p<0.001), with sensitivity and specificity of 84.4% and 92.3%, respectively, when these patients were included in the polyp group. This study suggests that the Oct4 and CD26 panel is a promising biomarker for distinguishing CRC from normal and polyp patients, whereas the c-MYC and CXCR4 panel may identify polyp and CRC from normal individuals.